Effect of Pulsed Electric Field Assisted Low Temperature Thawing on Pork Quality - Pinpin LIU; Jiahua ZHOU; Chao ZHANG; Baogang WANG; Xingming SHI; Haiqiang HONG; Yunxiang WANG; Ranran XU; Lihua JIANG (Shipin gongye ke-ji)
The effect of pulsed electric field (PEF) assisted low temperature on the quality of frozen pork longissimus dorsi muscle during thawing was investigated in this study. The muscle frozen at −18 ℃ for 7 d was treated with 0 (Control), 3, 5, 10 kV PEF at 4 ℃ (P3, P5, P10). The effects of different treatments on thawing time, color, texture, water loss and water distribution of muscle were analyzed. Results showed that PEF treatment reduced thawing time and improved the quality of muscle. Thawing time of frozen muscle treated with 10 kV PEF was 44.4% shorter than that of control. Cooking loss of muscle did not change significantly by PEF treatment (P>0.05). The hardness of thawed muscle with PEF treatment was significantly lower than that in control (P<0.05). Surface color fading and microstructure damage of muscle were reduced by PEF treatment. These results suggested that 10 kV PEF at 4 ℃ had the shortest thawing time, the lowest thawing loss, the state of meat sample was closer to fresh sample, and the quality was better.